"Such Inexplicable Pain": Kon Ichikawa’s The Burmese Harp - Parmelee, Stephen (Christian scholar's review, 2011)
Kon Ichikawa’s 1956 film The Burmese Harp is a powerful depiction of the spiritual journey of a Japanese soldier in Burma immediately following the end of World War II. Stephen Parmelee discusses the nature of this soldier’s search for meaning in the face of suffering; the parallels and differences between this soldier’s search and the Christian’s understanding of ultimate meaning; and Ichikawa’s unexpected use of Christian and a cappella music to punctuate the dramatic events that occur in the film.